2014
DOI: 10.1108/lhs-04-2014-0033
|View full text |Cite
|
Sign up to set email alerts
|

Embedding physician leadership development within health organizations

Abstract: Access to this document was granted through an Emerald subscription provided by emerald-srm:448207 [] For AuthorsIf you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…General principles have been outlined here. The recent paper by Snell et al 28 provides a good framework for embedding physician leadership. The new short form of MES also provides a fl exible tool by which organisations can assess progress in their pursuit of medical engagement.…”
Section: Resultsmentioning
confidence: 99%
“…General principles have been outlined here. The recent paper by Snell et al 28 provides a good framework for embedding physician leadership. The new short form of MES also provides a fl exible tool by which organisations can assess progress in their pursuit of medical engagement.…”
Section: Resultsmentioning
confidence: 99%
“…This lack of engagement is critical to address because developing new ways to provide primary care, such as collaborative team approaches, is essential to sustaining an efficient and effective healthcare system 7–10. Physician relationships with healthcare organisations or health authorities provides a fundamental platform to support all other change initiatives 11–13. In a synthesis of the literature and expert panel report on physician engagement and leadership Denis et al 14 identified that much of the literature on engagement was based on managed care models in the USA and that gaps in knowledge existed about how different strategies, aimed at creating environments that support physician engagement, work on the ground in different contexts.…”
Section: Introductionmentioning
confidence: 99%
“…When physicians actively and effectively participate in leadership roles, they can improve healthcare system quality outcomes. [1][2][3][4][5] However, "physicians are trained as professional experts who fulfill a role in direct and immediate patient care" 6 infrequently integrating themselves into administrative structures to improve the "system." 7 Moreover, physicians may encounter challenges in learning to be effective in formal leadership roles due to lack of leadership experience and the preparation that helps develop requisite competencies and skills for management or organizational leadership positions.…”
Section: Introductionmentioning
confidence: 99%